PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015-2017) - Hidayatun Istikhomah, 15.05.52.0125; Srimindarti,, Ceacilia (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of liquidity, leverage, and profitability on firm value. This research was conducted in Indonesia by using an analysis unit of manufacturing companies that have gone public. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling with a research period of 2015 to 2017 and obtained as many as 105 companies. The results showed that liquidity has a significant positive effect on firm value, leverage has no significant negative effect on firm value and profitability has no significant negative effect on firm value.